2020
DOI: 10.9734/air/2020/v21i330191
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Government Procurement Adoption in Ghana: Critical Success Factors

Abstract: Aims:The study investigated the critical success factors for adopting an e-procurement in public sector procurement activities in Ghana. Study Design: The study used descriptive survey design. Place and Duration of Study:The study was carried out among some selected public sector organisations in Ghana from October 2019-January 2020. Methodology: A total sample size of 215 procurement staff from public entities including: Department of Feeder Roads, Ghana Cocoa Board, Ghana Health Service, Koforidua Technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For instance, [22] found that top management support, supplier readiness, employee knowledge and skills, compatibility, relative advantage, and complexity were the factors that strongly influenced the adoption of E-procurement in Sri Lankan public sector organizations. Similar to this, [23] conducted research on critical success factors for Ghana's adoption of electronic government procurement. The most important success element for the adoption of E-procurement was identified by the results as being quick, reliable and inexpensive internet services.…”
Section: Ii1 E-procurement Adoption In Various Institutionsmentioning
confidence: 98%
“…For instance, [22] found that top management support, supplier readiness, employee knowledge and skills, compatibility, relative advantage, and complexity were the factors that strongly influenced the adoption of E-procurement in Sri Lankan public sector organizations. Similar to this, [23] conducted research on critical success factors for Ghana's adoption of electronic government procurement. The most important success element for the adoption of E-procurement was identified by the results as being quick, reliable and inexpensive internet services.…”
Section: Ii1 E-procurement Adoption In Various Institutionsmentioning
confidence: 98%
“…Many studies have been conducted in Ghana concerning e-procurement. Ofori and Fuseini (2020) looked into the crucial success criteria for e-procurement adoption in Ghana's public sector procurement activities. A descriptive survey design was used in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within supply chain technology, electronic government portal is one of the evolutionary electronic application, shaping the practice of procurement in public sector organisation (Soong et al , 2020; Ofori and Fuseini, 2019; Chan and Owusu, 2022). Over the past two decades, electronic government portal has been an essential electronic tool to achieve standardisation and consistency, which, in turn, speed up public procurement process (Hanák et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, electronic government portal has been an essential electronic tool to achieve standardisation and consistency, which, in turn, speed up public procurement process (Hanák et al , 2018). An assessment of the relevance of electronic government portal in the public sector procurement system suggests that it is an innovative technique that has the potency to solve many challenges pertaining to the traditional procurement system (Ofori and Fuseini, 2019; Danso, Xuhua and Fuseini, 2020). Furthermore, the use of these technologies is contributing to greater transparency, efficiency and effectiveness in public spending by enabling more open, innovative and accountable public entities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation